The complete mitochondrial genome sequence of Otus scops (Aves, Strigiformes, Strigidae). Issue 1 (2nd January 2019) - Park, Chang Eon; Kim, Min-Chul; Ibal, Jerald Conrad Pernites; Pham, Huy Quang; Park, Hee Cheon; Shin, Jae-Ho
Abstract: The Eurasian scops owl Otus scops (Aves, Strigiformes, Strigidae) is small typical owl belonging to the family Strigidae. The complete mitochondrial genome sequence consisted of 17413 base pairs encoding 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNAs, and non-coding regions. The overall base composition of O. scops was G + C: 46.2%, A + T: 53.8%, apparently with a slight AT bias. Phylogenetic analysis showed that O. scops was closely related to the widespread owl genera Asio and Ninox.